Influence of Leadership, Motivation, and Working Environment Towards Employee Performance at Bukalapak.com - Muhammad Hafid; Antyo Pracoyo (STIE Indonesia Banking School, 2020)
In the development of the increasingly competitive business world, employees' performance and motivation are important to improve performance and motivate employees to maintain strength in business competi-tion. The Study aims to know analyzing the influence of leadership, motivation, and work environment on employee performance on Bukalapak.com. The method of study used is Survey by using questioner as the primary data. The samples used in this study were80Employees' Sales on thebukalapak.com. This study uses 16 question indicators by displays the Likert 1-6 interval scale. The analysis method of This study us-es the analysis method PLS (Partial Least Square) with SmartPLS 2.3 tool. From the results of the re-search, it can be proved that leadership has a positive and significant influence on the employee's perfor-mance on bukalapak.com, then motivation has a positive influence and significant impact on employee per-formance on bukalapak.com, as well as working environments that support positive and significant impact on employee performance bukalapak.com